Physicians’ perception on prescribing potentially inappropriate medications for older patients: a qualitative study from Malaysia - Mohd Roslan, Umairah; Zaini, Syahrir; Akkawi, Muhammad Eid (Kulliyyah of Pharmacy, International Islamic University Malaysia (IIUM), 2024)
Introduction: Many quantitative studies reported that potentially inappropriate medication (PIM) is quite prevalent among older adult patients. However, the issue is less explored qualitatively from the perspective of physicians.